THE USE OF GINGER SOFTWARE IN SUPPORTING SELF-CORRECTION IN WRITING: EFL STUDENTS’ PERSPECTIVE - Nasution, Sahraini Yamni Nurul Falah; Dewi, Utami (TELL - US JOURNAL, 2025)
Writing is an important skill in learning English as a Foreign Language (EFL), but many students struggle due to a lack of grammar knowledge, limited vocabulary, and low awareness of their mistakes. One way to help students overcome these challenges is self-correction, which allows them to find and fix their own mistakes. This study explores how Ginger Software supports self-correction in writing from the perspective of EFL students. Using a qualitative case study approach, the research involved seven students who actively used Ginger Software in their writing tasks. Data was collected through semi-structured interviews and analyzed using thematic analysis. The results show that Ginger Software helps students improve grammar accuracy, sentence structure, and writing efficiency. Features like grammar checker, spell checker, and sentence rephrasing support students in recognizing and correcting their mistakes independently. However, some students still find it difficult to improve the cohesion and coherence of their academic writing using the software alone. Therefore, combining technology with teacher guidance is recommended to make writing practice more effective